Novel Evolution Process of Zn-Induced Nanoclusters on Si(111)-(7×7) Surface - Zhou, Changjie; Wu, Yaping; Chen, Xiaohang; Lin, Wei; Zhou, Yinhui; Kang, Junyong; Zhu, Huili (Nano-Micro Letters, 2015)
A tiny number of Zn atoms were deposited on Si(111)-(7×7) surface to study the evolution process of Zn-induced nanoclusters. After the deposition, three types (type I, II, and III) of Zn-induced nanoclusters were observed to occupy preferably in the faulted half-unit cells. These Zn-induced nanoclusters are found to be related to one, two, and three displaced Si edge adatoms, and simultaneously cause the depression of one, two, and three closest Si edge adatoms in the neighboring unfaulted half-unit cells at negative voltages, respectively. First-principles adsorption energy calculations show that the observed type I, II, and III nanoclusters can reasonably be assigned as the Zn3Si1, Zn5Si2, and Zn7Si3 clusters, respectively. And Zn3Si1, Zn5Si2, and Zn7Si3 clusters are, respectively, the most stable structures in cases of one, two, and three displaced Si edge adatoms. Based on the above energy-preferred models, the simulated bias-dependent STM images are all well consistent with the experimental observations. Therefore, the most stable Zn7Si3 nanoclusters adsorbed on the Si(111)-(7×7) surface should grow up on the base of Zn3Si1 and Zn5Si2 clusters. A novel evolution process from Zn3Si1 to Zn5Si2, and finally to Zn7Si3 nanocluster is unveiled.